KKR Dalam Upaya Kontrol Pemerintah Pusat Terhadap Aceh (Studi Tentang Pembentukan Komisi Kebenaran dan Rekonsiliasi di Aceh) - , ARYOS NIVADA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Basically, this study focuses to cognize the form of control conducted by the Central Government in the establishment of a Truth and Reconciliation Commission (TRC) in Aceh. The purpose of this study consisted of two things, first